Ethanolysis of soybean oil into biodiesel: Process optimization via central composite design - Nakorn Tippayawong (2018)
A process for production of ethyl ester for use as biodiesel has been studied. The sodium hydroxide catalyzed transesterification of soybean oil with ethanol was carried out at different molar ratio of alcohol to oil, reaction temperature and catalyst amount for a constant agitation in two hours of reaction time. Central composite design and response surface methodology were used to determine optimum condition for producing biodiesel. It was found that ethanol to oil ratio and catalyst concentration have a positive influence on ester conversion as well as interaction effects between the three factors considered. An empirical model obtained was able to predict conversion as a function of ethanol to oil molar ratio, reaction temperature and catalyst concentration adequately. Optimum condition for soybean ethyl ester production was found to be moderate ethanol to oil ratio (10.5: 1), mild temperature range (70°C) and high catalyst concentrations (1.0%wt), with corresponding ester conversion of 93.0%.